THE EFFECT OF THE THIELEN MODEL (GROUP INVESTIGATION) USING SKILLFULL EXERCISES IN LEARNING SOME BADMINTON SKILLS FOR STUDENTS - Assistant of Sport Coach, Haider Hisham Abdul Ali (Proximus Journal Publishing, 2025)
The aim of the research is to identify the effect of the Thilin s model (group investigation) using skill exercises in learning some badminton skills for students. To identify the superiority of the experimental and control research groups in learning some badminton skills for students, as the researcher used the experimental method in the style of equivalent groups with a test (pre- and post-test), which is what you see as appropriate and consistent with the research specifications, solving the problem and achieving its goals. The research community was determined by the second-stage students of the Department of Physical Education and Sports Sciences, College of Basic Education, Al-Mustansiriyha University for the academic year 2024-2025,(89), and the research sample was selected in a systematic random manner (20) students, and they were divided into two experimental and control groups in a random manner, as the number of each group was (10) students, who represent the research sample. Among the most important conclusions, the application of the Thelen model (group investigation) through skill exercises showed a noticeable positive effect on students' performance in badminton skills, as the accuracy of the strikes and the strength of ball control increased. The model contributed to enhancing the spirit of cooperation among students, which led to improving teamwork and increasing motivation for learning and continuous improvement. As for the research recommendations, it is recommended to expand the application of the Thelen model in other sports fields to enhance educational and social benefits. The need to organize regular training sessions that focus on skill exercises, as repetition enhances the mastery of skills faster.
Keywords: Thelen model; skill exercises; badminton skills